Mental Health and Parental Factors among Adolescents during the COVID Pandemic in Malaysia - Sangaran, Lena Nanditha; Kadir, Azidah Abdul; Yaacob, Lili Husniati; Zin, Faridah Mohd; Othman, Azizah (International Journal of Child Health and Nutrition, 2022)
Purpose: The study aims to determine the prevalence of mental health problems among early adolescents and their associations with parental relationships. Methods: A cross-sectional study was conducted on 535 adolescents aged 13 to 14 on the east coast of Peninsular Malaysia using online surveys from February 2021 to April 202. Mental health status was assessed using the Depression, Anxiety and Stress Scale- 21 (DASS-21), and parental or guardian supervision, connectedness, bonding, respect for privacy, physical activity, and risk behaviours were asked using the Malaysian Global School-based Student’s Health Survey. Multiple logistic regression analysis was done to examine the associations of the variables. Results: The prevalence of depression, anxiety and stress were 28.2%, 38.1% and 18.5%, respectively. Adolescent with low parental/guardian connectedness and bonding were associated with depression (AOR = 3.82, 95% CI =1.80 – 8.08), anxiety (AOR 2.17,95% CI = 1.34 – 3.50) and stress (AOR 2.29, 95% CI = 1.13 – 4.65). Low parental supervision (AOR = 2.37, 95% CI = 1.19 – 4.54), low academic performance (AOR = 3.57, 95% CI = 1.10 – 11.62), stress (AOR = 8.56, 95% CI = 4.38 – 16.70) and anxiety AOR = 7.83, 95% CI = 4.48 – 13.70) were predictors for depression. Adolescent who had divorced or separated parents/guardians (AOR = 3.57, 95%CI = 1.10 – 11.62) and married parents/guardian but living apart due to working (AOR = 3.57, 95% CI = 1.10 – 11.62) were higher risk for stress. Conclusions: Depression and anxiety were prevalent among adolescents in Malaysia. Poor relationship with parents or guardians was a significant factor for mental health problems among adolescents during the COVID pandemic.